2015
DOI: 10.1007/s11250-015-0880-x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for very virulent infectious bursal disease virus in vaccinated chickens in Nigeria

Abstract: Reverse transcription polymerase chain reaction (RT-PCR) and partial sequencing of the VP2 hypervariable region was performed on clinical samples from two infectious bursal disease (IBD) outbreaks in Plateau state, Nigeria. IBD virus RNA was detected in all four bursa of Fabricius samples. Nucleotide sequencing and analysis of the four samples revealed high similarity to previous IBDV sequences from northern and southern Nigeria. The deduced amino acid sequences were compared to reference IBDV strains retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Comparison of the amino acid sequences of the viruses used in this study with previously published Nigerian IBDV isolates showed some similarity [20]. The only exceptions were substitution mutations seen at amino acid position T219 and S269 in some of the viruses used in this study but not seen in previously published Nigerian IBDV [18-21]. These mutations suggest that vvIBDV strains are continuing to evolve in Nigeria.…”
Section: Discussionsupporting
confidence: 49%
“…Comparison of the amino acid sequences of the viruses used in this study with previously published Nigerian IBDV isolates showed some similarity [20]. The only exceptions were substitution mutations seen at amino acid position T219 and S269 in some of the viruses used in this study but not seen in previously published Nigerian IBDV [18-21]. These mutations suggest that vvIBDV strains are continuing to evolve in Nigeria.…”
Section: Discussionsupporting
confidence: 49%
“…Phylogenetic analysis indicates that IBDV/VOM/NG/2017 is a vvIBDV strain due to its clustering with reference vvIBDVs used for comparison. The vvIBDV strains have been reported in vaccinated and unvaccinated poultry flocks in some parts of Nigeria [10,11,19]. For ease of classification and identification of the probable origin and relatedness of some vvIBDVs from Africa, African vvIBDVs are divided into three; VV-1, consists of IBDV from Ethiopia, Nigeria and Zambia, VV-2, consists of IBDV from Nigeria, Tanzania and Zambia, while VV-3, collectively consists of IBDV from Africa, Asia, Europe and some other countries [20].…”
Section: Discussionmentioning
confidence: 99%
“…These IBDVs have been generally considered atypical isolates that evolved in restricted geographic regions or during a short period of time under particular conditions. In Nigeria, IBD was first reported in 1973 and since then despite routine vaccination programme, IBDV has assumed an endemic status with vvIBDV being reported throughout the country [10,11,12]. An accurate identification of the field variants circulating in poultry production is essential to understand the epidemiology and control of the disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first described in Nigeria in 1973 (Ojo et al, 1973), IBD has ravaged and still continues to wreck havoc on the poultry industry in Nigeria, which has made it achieve an endemic status. There have been several reports of outbreaks of IBD in both vaccinated and unvaccinated poultry chickens in Nigeria (Adamu et al, 2013;Luka et al, 2014;Owolodun et al, 2015;Nwagbo et al, 2016). Previous and recent studies have implicated very virulent (vv) strains of IBD as being responsible for these outbreaks (Owoade et al, 2004;Adamu et al, 2013;Luka et al, 2014;Owolodun et al, 2015;Nwagbo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of outbreaks of IBD in both vaccinated and unvaccinated poultry chickens in Nigeria (Adamu et al, 2013;Luka et al, 2014;Owolodun et al, 2015;Nwagbo et al, 2016). Previous and recent studies have implicated very virulent (vv) strains of IBD as being responsible for these outbreaks (Owoade et al, 2004;Adamu et al, 2013;Luka et al, 2014;Owolodun et al, 2015;Nwagbo et al, 2016). In addition, a very recent study also implicated reassortant IBDV strains as contributing to the failure of IBD vaccine in protecting chickens against field IBDV infection in Nigeria (Nwagbo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%